Vaginal atrophy after menopause - Pinkerton, JoAnn (Henry Stewart Talks, 2012)
Vulvovaginal atrophy, Physiology of premenopausal vagina, Postmenopausal vagina, Development of vulvovaginal atrophy, Physiology of vulvar and vaginal changes, Physical examination of vulva and vagina, Vaginal maturation index (VMI or MI), Urethral changes with atrophy, Urogenital changes, Estrogen levels are decreased postmenopausally, First line therapy, Non hormonal treatment options, Vaginal atrophy treatment duration, Vaginal dilators, Bladder and urinary symptoms, Future options in testing